ANALISIS KESESUAIAN KUALITAS AIR SUNGAI DENGAN BAKU MUTU AIR UNTUK BUDIDAYA IKAN AIR TAWAR DI KABUPATEN TABALONG - Astriyani, Rezky Nur (SPECTA Journal of Technology, 2019)
The Minapolitan area in Tabalong District is one of the predominant areas from the point of economic interest based on Tabalong District's Urban Land Use Plan 2014-2034. The Minapolitan is the conception of fisheries economic development which it functions is in economy that consists of production, processing, and marketing the fisheries commodity, services, and other supporting activities. The fishery activities in Tabalong District are occurring mostly in Tabalong and Pemayaran River. The purpose of this research is to acknowledge the compatibility of water quality conditions based on water temperature, brightness, dissolved oxygen (DO), acidity level (pH), ammonia (NH3), and nitrite (NO2). The data analysis instrument is using descriptive through comparison of the current water quality condition upon the water quality standard of freshwater fisheries. The result shows that the water quality in Sungai Tabalong and Sungai Pemayaran consecutively for water temperature 28 oC and 30 oC, brightness 28 cm and 26 cm, dissolved oxygen (DO) 4,2 mg/L and 4 mg/L, acidity level (pH) 7, ammonia 3,33 mg/L and 0,25 mg/L and nitrite <0,3 mg/L. Overall the whole fish in the river of Tabalong District still could survive as well as the fisheries activities. However, controlling the activity around the river and the implementation of aquaculture technology is required to intensify the water quality.